ASSESSING THE MARKETING APPROACH OF PT PAL INDONESIA COMPANY THROUGH A SWOT ANALYSIS - Farhan Wahyu Nur Rahman; Maulana Ibrahim; Danny Ridho Rayza Pahlevi; Anggara Trisna Nugraha; Laili Agustin Widyaningrum (Pusat Penelitian dan Pengabdian Masyarakat (P3M) - PPNS, 2023)
This research examines how the SWOT method is employed to determine the marketing strategy of PT PAL INDONESIA, aiming to explore the application of SWOT, using qualitative methods for data collection and analysis. The study reveals its findings through a combination of online and offline surveys. Online surveys were conducted via a Google Form to gauge customer satisfaction, operational performance, and user preferences. Offline surveys involved interviews with various stakeholders at PT PAL Indonesia, including senior management, engineers, and employees. The outcomes illustrate the strategic utility of assessing a company's strengths, weaknesses, opportunities, and threats. This underscores the significance of considering these elements within a company. The SWOT analysis plays a crucial role in formulating business strategies and aids PT PAL Indonesia in comprehending both internal and external factors impacting the company. By effectively leveraging SWOT analysis, companies can enhance their competitiveness, tackle challenges, and capitalize on opportunities for sustained long-term growth and success.